2016
DOI: 10.1080/03004430.2016.1185102
|View full text |Cite
|
Sign up to set email alerts
|

Integrated STEM curriculum: improving educational outcomes for Head Start children

Abstract: In this study, the researchers aimed to design, plan and implement a Science, Technology, Engineering and Math (STEM) model to support Pre-K children's skills and knowledge in STEM as well as to improve Pre-K teachers' attitudes and professional skills to plan and integrate STEM concepts in their daily classroom activities. Four classrooms from a Head Start programme in an Eastern North Carolina County participated in the study. A quasi-experimental, pre-post-intervention design was adopted to implement the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 8 publications
3
90
2
11
Order By: Relevance
“…A group advocating that the STEM approach should implement in the preschool period suggests that preschool children behave like a natural scientist (Chesloff, 2013) and that many skills that can form the basis for further learning acquires during this period (Aldemir & Kermani, 2017). Children begin to develop some feelings about numbers long before they start counting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group advocating that the STEM approach should implement in the preschool period suggests that preschool children behave like a natural scientist (Chesloff, 2013) and that many skills that can form the basis for further learning acquires during this period (Aldemir & Kermani, 2017). Children begin to develop some feelings about numbers long before they start counting.…”
Section: Introductionmentioning
confidence: 99%
“…All these activities can count as a part of STEM activities. STEM activities can be included in preschool education by hands-on activities that help children develop an understanding of STEM and enhance their future learning (Aldemir & Kermani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the research findings found that the preparation of teachers for dealing with STEM and STEAM education in early childhood years is very limited. There were three studies of international research which were conducted with in-service preschool teachers (Atiles at al., 2013;Bers et al, 2013;Bagiatti & Evangelou, 2015;Aldemir & Kermani, 2016). In Thailand, only one study was conducted the STEM collaborative teacher professional development with in-service preschool teachers' understanding and teaching practices (Thammaprateep & Chartisathian, 2018).…”
Section: Professional Development Of Stem and Steam Education For Earmentioning
confidence: 99%
“…Bagaimanapun, kejayaan proses pembelajaran adalah apabila guru-guru memiliki kualiti pengajaran dan pembelajaran dalam penyampaian PdP (McIntyre, 2014). Murid dapat mencapai tingkat pemahaman yang lebih tinggi melalui STEM apabila disokong dengan guru-guru yang berkualiti (Aldemir & Kermani, 2016). Chang and Park (2014) mengemukakan bahawa untuk meningkatkan pengalaman PdP dalam pembelajaran STEM bagi guru-guru dapat dilakukan melalui; (i) gaya mengajar, metode, atau strategi pengajaran yang mantap, (ii) pengetahuan dan persiapan yang matang dalam penyampaian materi, (iii) sikap mesra guru-guru terhadap murid dan proses pembelajaran, (iv) beban kerja guru-guru yang bersesuaian.…”
Section: Pengenalanunclassified